A Foresight Study about the Skills and Competencies Needed for Quality Professionals in 2030: An Empirical Study of Saudi Arabia - Touahmia, M.; Aichouni, M.; Alghamdi, A.; Kolsi, L.; Alzamil, H. (Engineering, Technology & Applied Science Research, 2020)
This paper presents the results of a foresight study examining the future knowledge, skills, and competencies required by quality professionals to meet the goals and objectives of the Saudi Vision 2030. The study aims to develop a methodology allowing the forecasting of skills and competency demands in the future. Data collection was conducted through the design of a web-based questionnaire that was distributed online to academic and quality management specialists in Saudi Arabia. The questionnaire consisted of four sections and forty items aiming to identify the necessary competencies that quality professionals should develop to deal with the changing business environments. The validity and reliability of the questionnaire were confirmed by Cronbach’s alpha and the data were analyzed using descriptive tests (mean and standard deviation). One-way ANOVA method was also used to test the significant differences in participants’ attitudes. The results of the study clearly emphasize on the emerging need for new effective skills to face this new era of the rapid pace of technological changes. The outcomes of this study may be used by policy-makers, local authorities, employers, academics, and researchers to set up future-oriented education and training policies to bridge the gap between skills demand and supply which arises out of labor market changes.